Modelling of Payout Ratio: A Panel Regression Analysis for Indonesian Listed Bank - Noviyanti Santoso; Rizka Widya Permatasari; Lucia Aridinanti (IPTEK The Journal of Engineering, 2020)
The Indonesian economy is a bank-based economy, where the economy relies on the existence of the banking sector as a source of financing, so a healthy and efficient banking system is the key to success in the sustainability of national economic development. The company's financial performance can be improved by going public. In companies that go public, dividends are one of the motivations of investors to invest their funds in the capital market, because it is a form of return on investor investment and an increase in wealth. The purpose of this study is determining the best model of the dividend payout ratio (DPR) in the banking sector by predictor variables such as ROI, DER, ROE, PER, and CAR using panel regression analysis. Based on the results of the analysis it was concluded that the factors that influenced the banking sector DPR were ROI and CAR with a good model of 86,7%.